FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT DELAY DI INDONESIA (Studi Empiris Pada Perusahaan-Perusahaan LQ 45 Yang Terdaftar Di Bursa Efek Jakarta) - Andi Kartika (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2009)
Time difference between financial statement and auditing opinion date indicatesthe amount of time needed in auditing settlement period. This condition can affect thepunctuation of the information published and will influence market reaction towardsthe lengthy information. It will also the level of uncertainty based on the publishedinformation in the auditor’s financial statement in which containing company’s profitinformation. This study aims to measure the factors which affect audit delay. They aretotal asset, operation loss and profit, auditor’s opinion, profitability, and auditor’sreputation.The population of the study is the LQ 45 companies registered in the JakartaStock Exchange in the period of 2001-2005. Sampling technique employed in this studyis the purposive sampling with the total sample of 13 companies. The data analysis usesmultiple regressions.The result of the study shows that the total asset, operation loss and profit, andauditor’s opinion have significant influence towards audit delay. On the other hand,profitability and the auditor’s reputation do not have any influence towards audit delay.Key words: audit delay, the size of the company, operation loss and profit, auditor’sopinion, profitability, auditor’s reputation.